(3JaSjQ GdbQBfs - (3efUhQ Hf eMeO Hf YHO GdLHGQ GdSeYGfj GdTGaYj, CHh efUhQ , LeGd GdOjf J (B562 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ ShQI GdaGJMI s
(3BNQgG (B:s
(3hjfJgi HBNQ ShQI GdJhHI s
(3GdLRA GdChd ef fSNI cJHJ SfI (B1271(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B303 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B20s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B28 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B449s
Keywords: (3GdJaSjQ hYdhe GdbQBfs